Genomic insights into multidrug resistance and virulence of methicillin-resistant Staphylococcus pseudintermedius from companion animal otitis - Menezes, Juliana; Rodrigues, Manuel; Pinto-Lima, Tiago; Isidoro, Sara; Meneses, André; Belas, Adriana (Frontiers in Veterinary Science, 2026)
Staphylococci are major opportunistic pathogens of companion animals and an important reservoir of antimicrobial resistance genes with zoonotic relevance. Otitis externa is one of the most common conditions requiring antimicrobial therapy in veterinary practice, yet data integrating phenotypic and genomic analyses of staphylococcal isolates remain limited. This retrospective study aimed to characterize Staphylococcus spp. isolates recovered from cases of otitis externa in dogs and cats. Staphylococcus spp. strains (n = 76) recovered from otitis cases in dogs and cats, which were identified by 16S rRNA gene sequencing, were tested for antimicrobial susceptibility according to CLSI guidelines. Methicillin-resistant strains (n = 11) were further characterized by whole-genome sequencing (WGS) to determine sequence types, resistance determinants, and virulence-associated genes. Staphylococcus pseudintermedius was the predominant species identified. A high proportion of strains exhibited resistance to tetracyclines and β-lactams, and 39.5% were classified as multidrug-resistant (MDR). Methicillin-resistant strains carried mecA and predominantly belonged to the European methicillin-resistant S. pseudintermedius (MRSP) lineage ST551, alongside ST496, ST1786, ST1095, and three novel sequence types. Genomic analysis revealed a conserved virulence repertoire including leukocidins, biofilm-associated genes (icaBDCA, sdrD), lipoprotein maturation enzymes (lgt, lspA), and immune-modulatory exotoxins. Core SNP-based analysis showed that two strains from dogs originating from different owners differed by only two SNPs. The combination of phenotypic resistance and genomic virulence determinants observed in these strains highlights the clinical significance of Staphylococcus spp. in otitis externa and reinforces the need for prudent antimicrobial stewardship and robust infection-control measures in veterinary medicine. The study also illustrates how sustained genomic surveillance can generate insights that support both veterinary and public-health actions.